Recent changes in subsurface temperature and salinity in the Canary region - Benítez Barrios, Verónica; Hernández Guerra, Alonso; Vélez-Belchí, Pedro; Machín, Francisco; Fraile-Nuez, Eugenio (Geophysical Research Letters, 2008)
5 pages, 4 figures Based on hydrographic sections carried out during the last decade in the Canary region at 29° 10′N, we show that there has been a statistically significant rise in temperature and salinity on isobars between 1500 and 2300 db. The maximum increase, found at 1600 db, is occurring at a rate of 0.29°C and 0.047 per decade. Isobaric change decomposition into changes on neutral surfaces and changes due to the vertical displacement of the isoneutrals was performed. Results reveal that the lower part of North Atlantic Central Water (NACW) cooled and freshened on neutral surfaces, suggesting changes in the freshwater fluxes at the outcropping region. However, the signal in deep waters (1500–2300 db) was principally due to a downward displacement of the isoneutrals, although water mass modification is observed in the range of Mediterranean Water (MW) influence The first author is supported by a grant received from the Canary Government. This work has been supported by the European Union project CANIGO (MAS3-CT96-0060) and the Spanish Government project ORCA (CMT2005-04701-C02-01) Peer reviewed